Sistema de generación de efectos en tiempo real para guitarra acústica sin amplificador externo (2018)
This work shows how a sound effects system generator for electroacoustic guitars was made, in which it uses the guitar acoustic box to release the sound through a resonant speaker, also use IOT (internet of things) to bring the costumer a very comfortable way to manipulate it through an Android app in which he could select the effect he wants to use and manipulate their parameter. In actuality the sound effects dispositives that use the acoustic box of the guitar are very expensive, an example is the very popular “Tonewoodamp” that cost around 250 dollars, this is one of the reasons why this system was created, because is cheaper and another attractive is that the code Will be open, so if the user wants to create and implement his own sound effects, he Will be able to. The code was written in C language and use the audio library “Portaudio”. Also, the system has an added and it’s a guitar tuner that consist in the reproduction of the sounds of the strings tuned, so the guitarist could tune his guitar in an easier way, he can use this through the App.